2016
DOI: 10.1007/s00227-015-2779-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of sequential low-tide-period conditions on the thermal physiology of summer and winter laboratory-acclimated fingered limpets, Lottia digitalis

Abstract: exposure of 25-35 °C (summer) and 20 °C (winter) had greater upper critical thermal limits of cardiac performance as determined by final breakpoint temperature (~1.5-6 °C increase) and flatline temperature (~1-2 °C increase) than limpets with no previous exposure. The magnitude of temperature increase that conferred significant increases in thermal tolerance differed in summer and winter, reflecting seasonal differences in the thermal environment in nature. Fingered limpets' upper thermal tolerance is plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Meanwhile, in warm seasons, a greater change in ∆ABT was induced by heat hardening than in ∆FLT in S. constricta , indicating a better ability of S. constricta to shift thermal sublethal limits with synchronization of heat hardening and acclimatization. In fact, the thermal sublethal limit or lower heat tolerance traits show higher plasticity than the lethal limit in many species, including intertidal species (Han et al., 2013; Pasparakis et al., 2016; Semsar‐Kazerouni & Verberk, 2018; Stenseng et al., 2005). Temperatures exceeding the thermal sublethal tolerance of organisms usually mean ‘ecological death’ because, at that time, organisms cannot avoid adverse effects of predation or a further rise in temperature due to activity restriction or thermal damage (Archambault et al., 2013; Dong et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in warm seasons, a greater change in ∆ABT was induced by heat hardening than in ∆FLT in S. constricta , indicating a better ability of S. constricta to shift thermal sublethal limits with synchronization of heat hardening and acclimatization. In fact, the thermal sublethal limit or lower heat tolerance traits show higher plasticity than the lethal limit in many species, including intertidal species (Han et al., 2013; Pasparakis et al., 2016; Semsar‐Kazerouni & Verberk, 2018; Stenseng et al., 2005). Temperatures exceeding the thermal sublethal tolerance of organisms usually mean ‘ecological death’ because, at that time, organisms cannot avoid adverse effects of predation or a further rise in temperature due to activity restriction or thermal damage (Archambault et al., 2013; Dong et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Tanks were designed to be flow through and continuously flushed with fresh seawater during high and low tides. Heat budget models for limpets have shown that substrate temperature is the primary driver of limpet body temperature (Bjelde and Todgham, 2013;Denny and Harley, 2006) and therefore substrate temperatures were manipulated to modulate limpet body temperature during low tide periods (Bjelde and Todgham, 2013;Bjelde et al, 2015;Pasparakis et al, 2016). Substrate temperature and water height were manipulated using Arduino microcontrollers (Arduino YUN, Adafruit, New York, NY, USA; Miller and Long, 2015).…”
Section: Acclimation To Simulated Tidal Conditionsmentioning
confidence: 99%
“…The temperature data set provided two summers of temperature profiles indicative of the variable heating regimes experienced by limpets in nature at a upper mid-intertidal location (Bjelde and Todgham, 2013;Pasparakis et al, 2016). The average degree of heating during the low tide periods of the summer months of 2011 and 2012 for each 2-week time interval was calculated.…”
Section: Acclimation To Simulated Tidal Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such work (e.g., multi-stressor studies) has been done with several high intertidal animals, for instance Lottia sp. and Cellana grata limpets (Williams et al 2011, Denny & Dowd 2012, Pasparakis et al 2016, Drake et al 2017, porcelain and green crabs (Petrolisthes cinctipes and Carcinus maenas; Paganini et al 2014, Nancollas 2020, Nancollas & McGaw 2021, and the tidepool sculpin (Oligocottus maculosus; Somo et al 2020); but overall, this area is still little explored (e.g., the majority of multi-stressor studies appears to be focused on subtidal animals; see review by Gunderson et al 2016). Multi-stressor experiments can evaluate the interactive effects of various abiotic factors, many of which may be exacerbated with anthropogenic climate change.…”
Section: Future Research Directionsmentioning
confidence: 99%